Assessing Older Adults' Decision-Making Capacity for Independent Living: Practice Tensions and Complexities. (May 2022) - Usher, Ruth; Stapleton, Tadhg
Decision-making capacity (DMC) is a salient issue due to increasing ageing populations and associated dementia-related diseases. Legislative and policy developments emphasise older adults' rights to participate in decision-making. Fifty-two occupational therapists working with older adults from a range of practice settings in Ireland participated in focus groups to discuss their contribution to multidisciplinary assessments of older adult's DMC for independent living. Findings indicate lack of shared understanding of DMC and conflicting philosophies of practice and highlight the need for a comprehensive and multidisciplinary approach. Findings also highlight that older people are often excluded from care-planning, and independent living options are determined by availability of community services rather than their preferences. Future research will attempt to inform practice in assessing and supporting older adults' DMC for independent living.